Penanganan Siswa Hiperaktif di Sekolah Dasar melalui Model Contextual Teaching Learning (CTL) Berbantuan Metode Self Instruction - Muh Muhaimin; Aniatus Sholikhah; Hilmalia Rahma; Muchammad Yusuf Al Anan; Vadia Rahmi Inaya (Dawuh Guru: Jurnal Pendidikan MI/SD, 2023)
Hyperactive students are a challenge for teachers in learning because they can interfere with the learning process. Teachers can choose the right learning model and learning method so that learning can run well. This study aims to determine the implementation of the Contextual Teaching Learning (CTL) model assisted by the Self Instruction method in dealing with hyperactive students. This type of research is qualitative research with a case study approach using descriptive qualitative methods. Data collection techniques in this study used observation, questionnaires and interviews. The research subjects were 1st grade students totaling 2 children out of 29 students. The results of this study indicate that the use of the CTL learning model assisted by the self-instruction method creates a more effective atmosphere in learning. It is proven that during learning, an interactive classroom atmosphere is created conducive to the teacher's efforts in explaining the material to all students. The use of instruction through positive affirmation sentences is able to encourage students to consider their own decisions regarding the behavior they do.